2014
DOI: 10.18553/jmcp.2014.20.5.501
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Treatment Patterns of Adding a Third Agent to 2 OADs in Patients with Type 2 Diabetes

Abstract: This study found that in current practice, physicians seem to be reluctant to prescribe injectable agents for patients with uncontrolled T2DM despite combination OAD therapy. Despite higher treatment persistence among patients adding a third OAD, this persistence did not translate into better glycemic control and may not necessarily be a long-term cost-saving solution. These data indicate a need for more evidence-based and patient-centered treatment decisions for patients unable to achieve and maintain glycemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 22 publications
2
47
0
2
Order By: Relevance
“…Moreover, mean glycaemic values were lower among subjects intensified by the addition of a new NIAD than by adding insulin. Our results support previous studies reporting that, in patients taking ≥2 OADs, the addition of a further oral medication takes place when HbA1c values are between 8.4% and 9.1%, and therapy is stepped up with insulin at when HbA1c values are between 9.2% and 9.9% . This reflects extremely poor glycaemic control, far above the recommended targets advocated in local and international guidelines.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, mean glycaemic values were lower among subjects intensified by the addition of a new NIAD than by adding insulin. Our results support previous studies reporting that, in patients taking ≥2 OADs, the addition of a further oral medication takes place when HbA1c values are between 8.4% and 9.1%, and therapy is stepped up with insulin at when HbA1c values are between 9.2% and 9.9% . This reflects extremely poor glycaemic control, far above the recommended targets advocated in local and international guidelines.…”
Section: Discussionsupporting
confidence: 88%
“…Pharmacotherapy intensification is generally recommended when glycaemic level is inadequately controlled despite acceptable medication adherence . Supporting the clinical guidelines, observational studies have consistently shown a positive association between the decrease in HbA1c and treatment intensification in patients who did not achieve glycaemic control with metformin (MET)‐based antidiabetic care . Time in clinical inertia, that is, the failure to initiate or intensify treatment when indicated, needs to be shortened to increase the likelihood of attaining glycaemic control and lower HbA1c levels .…”
Section: Introductionmentioning
confidence: 99%
“…Almost 40% of patients in whom a GLP-1 receptor agonist was added switched therapy during the first year, compared with 25% of patients in whom insulin was added and 9% of those in whom a third OAD was added. However, the greater treatment persistence among patients with triple-OAD therapy did not translate into better glycemic control [36].…”
Section: Discussionmentioning
confidence: 93%